Amiodarone-Induced Multi-Systemic Toxicity Involving the Liver, Lungs, Thyroid, and Eyes: A Case Report - You, Hye-Su; Yoon, Jae Hyun; Cho, Sung Bum; Choi, Yoo-Duk; Kim, Yung Hui; Choi, Wonsuk; Kang, Ho-Cheol; Choi, Sung Kyu (Frontiers in Cardiovascular Medicine, 2022)
Objectives Amiodarone is widely used to treat arrhythmia. However, amiodarone is known for its severe toxicity to the liver, lungs, and thyroid. Amiodarone causes liver damage ranging from asymptomatic serum aminotransferase elevation to hepatic failure requiring liver transplantation. Although amiodarone toxicity has been reported, its simultaneous multi-organ toxicity is not well-known. Here, we introduce a novel case of multi-systemic amiodarone toxicity involving the liver, lungs, thyroid, and eyes. Case Presentation A 61-year-old woman visited the emergency room due to general weakness, nausea, visual disturbance, heat intolerance, and a non-productive cough. The patient had been using clopidogrel and amiodarone due to underlying atrial fibrillation. The total level of bilirubin was 0.71 mg/dL, aspartate aminotransferase was 358 U/L, alanine aminotransferase was 177 U/L, and prothrombin time was 27.1 s. Computed tomography showed diffuse increased liver intensity and scattered hyperattenuated nodular consolidations in both lungs. Transthoracic needle lung biopsy revealed fibrinoid interstitial inflammation with atypical change of type II pneumocytes and intra-alveolar foamy macrophages. In addition, the thyroid-stimulating hormone level was <0.008 μIU/mL, and free thyroxine was 4.67 ng/dL. The thyroid scan showed diffuse homogenous intake of technetium-99 m pertechnetate in both thyroid lobes. The ophthalmologic exam detected bilateral symmetrical corneal deposits in a vortex pattern. With these findings, we could diagnose amiodarone-induced hepatic, pulmonary, thyroid, and ophthalmologic toxicity. Liver function was restored after cessation of amiodarone, and thyroid function was normalized with methimazole administration. However, due to aggravated lung consolidations, systemic steroid treatment was administered, and improvement was seen 1 week after, at the follow-up exam. As her symptoms improved, she was discharged with a plan of steroid administration for 3 to 6 months. Conclusions This case implies the possibility of multi-systemic amiodarone toxicity. Thus, the toxicity of amiodarone to multiple organs must be monitored. Prompt cessation of the drug should be considered upon diagnosis.